Doubly–Negating Complicatedness of Undoing Love: A Stylistic Reading of I Can’t Unlove You by Kenny Rogers - Akun Akun (Bina Nusantara University, 2013)
This wasa research about the role of linguistic features in contributing to the overall meaning of a song entitled I Can’t Unlove You by Kenny Rogers. The goal of the research was to prove that special linguistic features used in the song played a significant role in conveying the meaning of the song. This wasa library research by identifying and elaborating the special linguistic construction found in the song lyric text. It is concluded that the use of double negation combined with invented negative verbs has successfully build up the idea of impossibility in undoing love. This double negative expression is needed because love intricacy and complicatedness can only be expressed in a stylistically special way where common expressions are unable to reach the intended meaning.